Preparation And Characterization Of Sugarcane Bagasse As Biodegradable Fillers On Natural Rubber Latex Films - Leong, Siew Thung (Universiti Sains Malaysia, 2017)
The studied was carried out to improve the biodegradability of Natural Rubber (NR) latex films by adding biodegradable filler in the NR latex compound. The requirement for economic and environmental-friendly materials have extended an interest in using of natural waste fibres, sugarcane bagasse. Sugarcane bagasse was abundant and cheap. Hence, the biodegradable filler used in this studied was sago starch and sugarcane bagasse. Sago starch was obtained from the supplier, while the sugarcane bagasse was prepared in the laboratory. There were two methods use to prepare the filler dispersion, which were ball-milling with dispersing agent and treatment process by using 2 % sodium hypochlorite solution, which referred as treated sugarcane bagasse. NR latex film with sago starch shown better mechanical properties compared to NR latex film with sugarcane bagasse. The tensile strength, elongation at break and tear strength of NR latex film with treated sugarcane bagasse shown better properties compared to NR latex film with sugarcane bagasse. In the mass loss test, NR latex film with sago starch has the highest biodegradability, follow by NR latex film with treated sugarcane bagasse and then NR latex film with sugarcane bagasse. It proved that the addition of biodegradable filler can improved the biodegradability of NR latex film. The optimum loading of NR latex film with treated sugarcane bagasse was obtained at 5 pphr with high tensile strength, elongation at break, tensile modulus and tear strength. At higher loading of treated sugarcane bagasse tends to form agglomerate and act as failure point in NR latex film. To conclude, sugarcane bagasse shown a potential as bio fillers to replace sago starch in NR latex film.